Detection of Intrusions and Malware, and Vulnerability Assessment 10th International Conference, DIMVA 2013, Berlin, Germany, July 18-19, 2013. Proceedings - Rieck, Konrad; Stewin, Patrick; Seifert, Jean-Pierre.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 10th International Conference on Detection of Intrusions and Malware, and Vulnerability Assessment, DIMVA 2013, held in Berlin, Germany, in July 2013. The 9 revised full papers presented together with 3 short papers were carefully reviewed and selected from 38 submissions. The papers are organized in topical sections on malware; network security, Web security; attacks and defenses; and host security.
Malware -- Network security -- Web security -- Attacks and defenses -- Host security.
Keywords: Computer science; Computer Communication Networks; Computer network architectures; Software engineering; Data protection; Information Systems; Computer Science; Systems and Data Security; e-Commerce/e-business.; Computer Communication Networks; Computer System Implementation; Management of Computing and Information Systems; Software Engineering